2021
DOI: 10.1021/acsenergylett.1c01983
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Impact of Fe Incorporation on Intrinsic Performance of Reconstructed Water Oxidation Electrocatalyst

Abstract: Because of the salient impact on the performance of oxygen evolution reaction (OER), the surface dynamics of precatalysts accompanying the surface oxidation and dissolution of catalytic components demands immense research attention. Accordingly, the change in the structural integrity under high current density generally results in inconsistent OER performances. To address this challenge, here, we present the intricate design of precatalysts, strategically followed by reconstruction treatment in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 57 publications
3
51
0
Order By: Relevance
“…In addition, composites consisting of multivariate transition metals can promote the exceptional modification of active sites within the matrix, and thus improve reaction efficiency and durability [ 41 ]. Based on this, the addition of Fe elements has been confirmed as a proper approach to enrich the active sites and boost highly efficient OER performance [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, composites consisting of multivariate transition metals can promote the exceptional modification of active sites within the matrix, and thus improve reaction efficiency and durability [ 41 ]. Based on this, the addition of Fe elements has been confirmed as a proper approach to enrich the active sites and boost highly efficient OER performance [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…45 On the one hand, DFT calculations showed that the substituted Fe atoms changed electronic density of neighboring metals and affected reaction barriers to enhance the OER process. 46 On the other hand, Goldsmith et al proposed that the in situ produced Fe 4+ facilitated by the NiOOH lattice during the catalytic reaction can promote the OER performance. 47 Although there is still some debate, the significant improvement of Fe doping in OER performance is well recognized.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the fundamental understanding of CP and CV characteristics obtained from electrochemical conditioning of simple Ni foil, we extended our study to investigate the effects of CP and CV electrochemical conditioning for Ni-based compound precatalysts capable of efficient OER electrocatalysis. Considering the different degrees of in situ oxidation of OER precatalysts (e.g., partial or complete in situ oxidation) after random electrochemical conditioning in previous reports, [15][16][17][18][19][20][21][22][23][24] as well as the distinct characteristics of CP and CV studied in Section 2.1, it was hypothesized that the degree of in situ oxidation of OER precatalysts can be affected by the choice of electrochemical conditioning methods. Furthermore, it has been reported that transition metal compound precatalysts can form a porous and electrolyte-permeable structure as their anions dissolve into the electrolyte during in situ oxidation via electrochemical conditioning.…”
Section: Study Of Cp and CV Characteristics For Nise Precatalysts On ...mentioning
confidence: 99%
“…So far, different electrochemical conditioning methods (e.g., CP, CA, and CV) have been employed without clear distinction for various OER electrocatalysts and random electrochemical activation results (e.g., degree of in situ oxidation and Fe incorporation) have been reported. 10,[15][16][17][18][19][20][21][22][23][24] Kim et al conducted CV electrochemical conditioning for Co3C and observed its complete in situ oxidation to amorphous CoOx. 22 Kawashima et al conducted CV electrochemical conditioning for Ni3N/Ni foam in Fepurified and Fe-unpurified KOH electrolyte and observed its partial in situ oxidation and Fe incorporation into Ni3N/Ni.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation